Human rhinovirus detection in the lower respiratory tract of hematopoietic cell transplant recipients: association with mortality - Seo, Sachiko (Haematologica, 2017)
Human rhinoviruses are the most common respiratory viruses detected in patients after hematopoietic cell transplantation. Although rhinovirus appears to occasionally cause severe lower respiratory tract infection in immunocompromised patients, the clinical significance of rhinovirus detection in the lower respiratory tract remains unknown. We evaluated 697 recipients transplanted between 1993 and 2015 with rhinovirus in respiratory samples. As comparative cohorts, 273 recipients with lower respiratory tract infection caused by respiratory syncytial virus (N=117), parainfluenza virus (N=120), or influenza (N=36) were analyzed. Factors associated with mortality were analyzed using Cox proportional hazard models. Among 569 subjects with rhinovirus upper respiratory tract infection and 128 subjects with rhinovirus lower respiratory tract infection, probabilities of overall mortality at 90 days were 6% and 41%, respectively (P<0.001). The survival rate after lower respiratory tract infection was not affected by the presence of co-pathogens (55% in patients with co-pathogens, 64% in patients without, P=0.34). Low monocyte count (P=0.027), oxygen use (P=0.015), and steroid dose greater than 1 mg/kg/day (P=0.003) before diagnosis were significantly associated with mortality among patients with lower respiratory tract infection in multivariable analysis. Mortality after rhinovirus lower respiratory tract infection was similar to that after lower respiratory tract infection by respiratory syncytial virus, parainfluenza virus or influenza in an adjusted model. In summary, transplant recipients with rhinovirus detection in the lower respiratory tract had high mortality rates comparable to viral pneumonia associated with other well-established respiratory viruses. Our data suggest rhinovirus can contribute to severe pulmonary disease in immunocompromised hosts.